A transparent-hazy reversible phase change photothermal regulation film based on limited crystallization regulation and a preparation method thereof

CN122978486APending Publication Date: 2026-10-27HENAN UNIVERSITY OF TECHNOLOGY +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611183280.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-05
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0006]然而,目前尚缺乏一种能够兼顾高透光性、高储热密度以及透明-雾化可逆转换功能的相变光热调控材料,也缺乏针对相变组分结晶行为进行精准调控,从而实现透明性、储热性能及可逆光学响应性能协同优化的制备方法

Benefits of technology

1、通过梯度退火诱导受限结晶结构形成,实现长链烷烃相变体系透明化,提高材料可见光透过能力。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978486A_ABST
    Figure CN122978486A_ABST
Patent Text Reader

Abstract

The application discloses a transparent-fog reversible conversion phase change light and heat regulation film based on limited crystallization regulation and a preparation method thereof. The preparation method comprises the following steps: melt blending a phase change component and a transparent polymer support component, film forming treatment, gradient annealing treatment and programmed cooling. The gradient annealing comprises a high-temperature homogenization stage and a nucleation induction stage. In the high-temperature homogenization stage, the film is heated to 10-60 DEG C higher than the melting temperature of the phase change component and kept for 0.5-24 h. In the nucleation induction stage, the film is cooled to 0-20 DEG C higher than the crystallization temperature of the phase change component and kept for 0.5-12 h. The programmed cooling rate is 0.1-5 DEG C / min. The obtained film has a limited crystallization structure, the phase change component is uniformly dispersed in the OBC / PVB double network in the form of submicron microcrystals, the microcrystal size is 100-500 nm, the film is in a transparent state when the temperature is higher than the phase change temperature, and the film is in a fog state when the temperature is lower than the phase change temperature, so that the reversible conversion of the transparent state and the fog state is realized, and the film has the functions of phase change heat storage, light transmission regulation and temperature buffering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of phase change energy storage materials and photothermal control materials. Specifically, it relates to a transparent-to-fog reversible phase change photothermal control film based on restricted crystallization control and its preparation method. The film controls the crystallization behavior of the phase change components in the polymer network through gradient annealing, constructs a restricted crystallization structure, and realizes the reversible conversion between the transparent state and the fog state. It can be applied to the thermal management of transparent enclosure structures. Background Technology

[0002] Transparent glass is widely used in transparent enclosure structures such as automobiles, buildings, greenhouses, livestock and poultry breeding facilities, and skylights. While providing lighting, views, and spatial openness, it also introduces a large amount of solar radiation heat, causing the interior temperature to rise rapidly. Especially under strong sunlight conditions in summer, significant heat accumulation can easily occur in car cabins, livestock and poultry sheds, and building interiors, thereby increasing air conditioning cooling loads and energy consumption. Therefore, developing functional materials that combine light transmittance with solar heat regulation capabilities is of great significance for improving the energy-saving performance of transparent enclosure structures.

[0003] Phase change materials (PCMs) can absorb or release a large amount of latent heat through a solid-liquid phase change process, thereby buffering temperature fluctuations and are a typical passive thermal management material. Among them, long-chain alkane PCMs are widely used in building energy conservation, solar energy utilization, electronic device heat dissipation, and battery thermal management due to their advantages such as high latent heat of phase change, good chemical stability, excellent cycle performance, low supercooling, and low cost. However, traditional long-chain alkane PCMs tend to form large crystal structures during the cooling and crystallization process. Since the crystal size is close to the wavelength of visible light, significant light scattering occurs within the material, resulting in an opaque or semi-transparent state, which is difficult to meet the light transmittance requirements of transparent building envelopes.

[0004] To improve the transparency of phase change materials (PCMs), existing technologies typically employ methods such as transparent polymer encapsulation, microencapsulation, sol-gel methods, and transparent matrix composites. While these methods can improve the light transmittance of materials to some extent, they generally suffer from problems such as complex preparation processes, high costs, decreased latent heat of phase change, insufficient long-term stability, and difficulty in simultaneously achieving transparency and heat storage performance. Furthermore, most existing transparent PCMs aim to maintain a long-term transparent state, with their functions primarily focused on light transmission and heat storage or solar thermal management. Research on utilizing phase change processes to achieve reversible transitions between transparent and foggy states remains relatively limited.

[0005] For transparent building envelopes such as automotive glass, building windows, and greenhouse coverings, materials not only need to have good light transmittance but also need to meet requirements for solar thermal regulation, visual comfort, and privacy protection. While a continuously transparent state is beneficial for lighting and field of vision, it can easily cause glare under strong sunlight and may not meet the privacy requirements of some scenarios. Therefore, if a reversible transition between a transparent and a fogged state could be achieved, it would be possible to maintain lighting and heat storage functions while also meeting the needs for light environment regulation.

[0006] However, there is currently a lack of phase change photothermal control materials that can simultaneously achieve high light transmittance, high heat storage density, and transparent-to-fog reversible conversion functionality. Furthermore, there is a lack of preparation methods that precisely control the crystallization behavior of the phase change components to achieve synergistic optimization of transparency, heat storage performance, and reversible optical response. Therefore, developing a transparent-to-fog reversible phase change photothermal control film based on restricted crystallization control, and achieving synergistic integration of heat storage, light transmittance, and reversible optical response functions by regulating the crystallization behavior of the phase change components in the polymer network, is of great significance for passive thermal management and light environment control of transparent enclosure structures. Summary of the Invention

[0007] The purpose of this invention is to provide a transparent-to-atomized reversible phase change photothermal control film based on restricted crystallization control and its preparation method. By actively controlling the crystallization behavior of phase change components in the polymer network through a gradient annealing process, a restricted crystallization structure is constructed to achieve temperature-driven reversible conversion between the transparent state and the atomized state, while taking into account the functions of phase change heat storage, light transmission control and temperature buffering.

[0008] To achieve the above objectives, the present invention adopts the following technical solution: A method for preparing a transparent-fogging reversible phase change photothermal controlled thin film based on restricted crystallization control includes the following steps: (1) The phase change component and the transparent polymer support component are heated to a molten state and mixed evenly to obtain a molten mixture; (2) The molten mixture is taken out from the reactor and pretreated by casting at room temperature to obtain a gel-like precursor of phase change controlled film; (3) The obtained gel-like precursor is subjected to gradient annealing, including: a) High-temperature homogenization stage: The film is heated to 10-60°C above the melting temperature of the phase change component and held for 0.5-24 hours to promote interfacial reconstruction, chain rearrangement and uniform dispersion between the phase change component and the polymer support component. b) Nucleation induction stage: Cool down to 0-20°C above the crystallization temperature of the phase change component and maintain for 0.5-12 h to induce uniform nucleation and increase the nucleus density; (4) The phase change components are cooled at a rate of 0.1 to 5 °C / min to complete the crystallization process and obtain a transparent-atomized reversible phase change photothermal control film with a restricted crystal structure.

[0009] Preferably, the phase change component is a straight-chain alkane, a branched-chain alkane, paraffin, or a mixture thereof with 16 to 40 carbon atoms; the transparent polymer support component includes one or more of olefin block copolymers (OBC), polyvinyl butyral (PVB), polyurethane, and polymethyl methacrylate.

[0010] Preferably, the transparent polymer support component comprises olefin block copolymer OBC and polyvinyl butyral PVB, and the mass fraction of each component in the melt mixture is: phase change component 65-80 wt%, OBC 10-25 wt%, PVB 5-15 wt%.

[0011] Preferably, a low-frequency periodic vibration field with a frequency of 20 to 85 Hz is applied synchronously in step (4) to promote uniform distribution of crystal nuclei, suppress local grain agglomeration and preferential growth, thereby constructing a confined crystal structure.

[0012] Preferably, in step a), the annealing temperature of the high-temperature homogenization stage is 80-120°C; in step b), the nucleation induction stage is located near the crystallization temperature range of the phase transformation component, and the number of crystal nuclei, grain size and spatial distribution are adjusted by controlling the residence time.

[0013] Preferably, in step (3), an inducing nucleation component is further added, wherein the inducing nucleation component includes one or more of nano-silica, nano-alumina, nano-cellulose, and graphene quantum dots.

[0014] This invention also provides a transparent-fogging reversible phase change photothermal control film, prepared by the method described above. The film has a confined crystalline structure, wherein the phase change component is uniformly dispersed in the form of submicron-sized microcrystals in an OBC / PVB dual-network system, and the microcrystal size is 100–500 nm. The OBC / PVB dual-network system is composed of olefin block copolymer OBC and polyvinyl butyral PVB, wherein OBC provides a flexible supporting framework and PVB provides a transparent auxiliary support.

[0015] Preferably, the transparent-to-atomized reversible phase change photothermal control film has phase change heat storage, light transmission control and temperature buffering functions. It is transparent when the temperature is above the phase change temperature and atomized when the temperature is below the phase change temperature. The reversible conversion between the transparent and atomized states is driven by the light scattering changes generated during the melting and crystallization of the phase change components.

[0016] The present invention also provides the application of the above-mentioned transparent-fog reversible phase change photothermal control film in thermal management of automotive glass, building windows, sunroof glass, greenhouse covering structures and transparent enclosure structures.

[0017] Preferably, the thin film reduces solar radiation heat input and mitigates internal space temperature fluctuations through the synergistic effect of phase change heat storage and light transmission regulation.

[0018] This invention is based on a restricted crystallization control mechanism. It actively controls the crystallization behavior of the phase change component (paraffin) in the polymer double network (OBC / PVB) through a gradient annealing process, so that the crystallite size is controlled in the submicron level (100-500 nm). This allows the reversible conversion between the transparent and atomized states to be achieved by utilizing the "appearance-disappearance" of the crystals during the phase change process, while also taking into account the functions of phase change heat storage and temperature buffering.

[0019] This invention, based on the mechanism of gradient annealing actively controlling confined crystallization, achieves the synergistic integration of phase change thermal storage and optical control, specifically including the following aspects: 1. Dual-network support mechanism: OBC constructs a flexible encapsulation network, providing mechanical support and constraining the paraffin crystallization space; PVB constructs a transparent auxiliary network, improving interface compatibility and enhancing optical uniformity. The two interpenetrate to form a multi-level confined space, reducing the size of the paraffin crystallization unit to the submicron level.

[0020] 2. Gradient Annealing Control Mechanism: In the high-temperature homogenization stage, the film is heated to a range above the paraffin melting temperature and maintained, allowing all components to fully melt, interfaces to reconstruct, and uniformly disperse, eliminating the adverse effects of the previous thermal history on crystallization. In the nucleation induction stage, the temperature is lowered to near the paraffin crystallization temperature and maintained, using moderate supercooling to increase the nucleus formation density while avoiding excessive nucleus growth. In the programmed cooling stage, the temperature is slowly reduced to room temperature to control the crystal growth rate, allowing a large number of nuclei to grow uniformly to submicron size within a confined space. Based on this, a low-frequency periodic vibration field or nucleation-inducing components can be applied simultaneously to further promote uniform nucleus distribution, suppress local agglomeration, and obtain a more refined confined crystalline structure.

[0021] 3. Restricted Crystallization Optical Mechanism: The spatial constraint of the dual-network and the synergistic effect of high crystal nucleus density stabilize the size of paraffin crystallites within the range of 100–500 nm. This size is near the visible light wavelength scale, resulting in moderate and controllable light scattering intensity: moderate scattering occurs when the crystallites are present, and the material is in a misted state; scattering weakens after the crystallites melt and disappear, and the material becomes transparent. This enables temperature-driven reversible conversion between transparency and misting.

[0022] 4. Photothermal regulation mechanism: Under solar irradiation, paraffin undergoes a solid-liquid phase transition near its phase transition temperature, absorbing a large amount of latent heat, which significantly slows down the rate of temperature increase of the thin film and reduces heat transfer to the indoor space. At the same time, the thin film remains transparent at high temperatures, which is conducive to light transmission and solar heat collection; at low temperatures, it turns into a fog, which takes into account both privacy protection and glare suppression, adapting to different photothermal environment requirements.

[0023] Compared with the prior art, the present invention has the following advantages: 1. By inducing the formation of a confined crystal structure through gradient annealing, the long-chain alkane phase transition system can be made transparent, thereby improving the visible light transmittance of the material.

[0024] 2. By synergistically regulating crystallization behavior through nucleation induction and programmed cooling, excessive grain growth is inhibited and light scattering during the crystallization process is reduced.

[0025] 3. It achieves reversible conversion between transparent and atomized states, providing both heat storage and temperature regulation with privacy protection functions.

[0026] 4. It combines phase change heat storage, light transmission regulation and temperature buffering functions, which can reduce the solar heat input of transparent enclosure structures. It is suitable for various spatial environments that are sensitive to temperature fluctuations, including building interiors, greenhouses and livestock and poultry breeding facilities.

[0027] 5. The preparation process is simple and can be achieved using conventional melt blending and hot pressing processes, showing good prospects for engineering applications. Attached Figure Description

[0028] Figure 1 This is a process flow diagram of the preparation of the transparent-fogging reversible phase change photothermal control film based on restricted crystallization control in this invention; Figure 2 This is a diagram illustrating the gradient annealing-induced restricted crystallization mechanism in this invention. Figure 3 This is a schematic diagram illustrating the principle of reversible transparency-fogging in this invention. Figure 4 This is a SEM image of the microcrystalline structure of the thin film in the atomized state of the present invention; Figure 5 This is a SEM image of the transparent microcrystalline structure of the thin film of the present invention; Figure 6 SEM image of the microcrystalline structure of a conventional non-transparent phase change material without gradient annealing; Figure 7 This is an appearance diagram of the atomized state of the thin film material prepared in this invention; Figure 8 This is an appearance diagram of the transparent state of the thin film material prepared in this invention; Figure 9 The XRD diffraction pattern of the thin film prepared in this invention; Figure 10 This is a DSC test data graph of the thin film prepared in this invention; Figure 11 A schematic diagram of an experimental system for testing the photothermal performance of a glass module with a transparent-fog reversible phase change photothermal control film attached. Figure 12 The figure shows the experimental results of the photothermal performance test of a glass module with a transparent-fog reversible phase change photothermal control film attached. Figure 13 SEM image of the transparent microcrystalline structure of the thin film prepared by the method described in Example 2; Figure 14 SEM image of the transparent microcrystalline structure of the thin film prepared by the method described in Example 3; Figure 15 This is a SEM image of the transparent microcrystalline structure of the thin film prepared by the method described in Example 4. Detailed Implementation

[0029] The present invention will be further explained and described below with reference to the accompanying drawings and specific embodiments: Example 1: A method for preparing a transparent-to-fogging reversible phase change photothermal controlled thin film based on restricted crystallization control, such as... Figure 1 As shown, it includes the following steps: (1) Raw material preparation The phase change component can be selected from straight-chain alkanes with 16-40 carbon atoms (such as eicosane, docosane, octacosane, etc.), branched alkanes, paraffin wax, or mixtures thereof. This embodiment uses paraffin wax (PA) as an example, with a phase change temperature of approximately 28°C and a latent heat of phase change of approximately 180 kJ / kg. Other long-chain alkane phase change materials have similar molecular structures and crystallization behaviors to paraffin wax, and composite films with restricted crystallization structures and transparent-to-mistyling reversible conversion properties can all be prepared using the same process.

[0030] Olefin block copolymer (OBC) was selected as the flexible support framework, with a melting point of approximately 113 °C; polyvinyl butyral (PVB) was selected as the transparent auxiliary support component.

[0031] Among them, PA provides phase change thermal storage function, OBC constructs flexible encapsulation network, and PVB is used to improve system transparency and enhance interface compatibility. Together, they form a dual-network confined crystalline structure.

[0032] (2) Melt blending The ingredients are prepared according to the following mass fractions: PA 65–80 wt%, OBC 10–25 wt%, and PVB 5–15 wt%.

[0033] PA, OBC and PVB are added to a mixing apparatus and melt-blended at 120 °C for 30–60 min to ensure that the components are fully mixed and form a homogeneous system.

[0034] (3) Cast film laying The molten mixture is placed in a flat vulcanizing machine and cast at room temperature to obtain a gel-like precursor of a phase change modulated film with a thickness of 0.1–0.15 mm.

[0035] (4) Gradient annealing induces restricted crystallization The obtained gel-like precursor was subjected to gradient annealing in a constant temperature environment, such as... Figure 2 As shown, it specifically includes: First stage: High-temperature homogenization stage The gel-like precursor was kept at 80–120 °C for 0.5–24 h. This stage promoted interfacial reconstruction and chain rearrangement among PA, OBC, and PVB, reduced local phase separation, and improved system homogeneity.

[0036] Second stage: Nucleation induction stage The temperature was lowered to 35–45 °C and maintained for 0.5–12 h. This temperature range is close to the crystallization initiation temperature of PA, which can significantly increase the nucleus formation density and inhibit the continuous growth of a small number of nuclei.

[0037] Phase Three: Program Cooling-Down Phase The temperature was slowly reduced to room temperature at a rate of 0.1–5 °C / min. During the cooling process, a low-frequency periodic vibration field with a frequency of 20–85 Hz was simultaneously applied to improve the uniformity of the spatial distribution of crystal nuclei and suppress localized preferential growth. Through this gradient thermal regulation, PA was able to form a uniformly dispersed confined microcrystalline structure in the dual-network system.

[0038] (5) Analysis of the mechanism of reversible conversion between transparency and atomization After gradient annealing-induced restricted crystallization, PA forms a uniformly dispersed microcrystalline structure in the OBC / PVB dual-network system, endowing the material with temperature-responsive transparent-to-fogging reversible conversion properties. The mechanism is shown in the attached figure. Figure 3 As shown.

[0039] When the ambient temperature is higher than the phase transition temperature Tm, PA is in a molten state, the original crystal structure gradually disappears, and the phase transition components are uniformly dispersed in the OBC / PVB network in liquid form. At this time, the refractive index distribution inside the system tends to be uniform, the scattering at the crystal interface is significantly reduced, and visible light can effectively pass through the material, so the film is transparent.

[0040] When the ambient temperature drops below the phase transition temperature, PA gradually crystallizes, forming a large number of uniformly dispersed confined microcrystals under the constraint of the polymer network. As the number of crystals increases, a large number of interfaces are formed between the crystalline and amorphous phases, enhancing light scattering within the system, and the material gradually changes from a transparent state to a translucent or atomized state.

[0041] During the heating process, the PA crystals remelt, the scattering interface gradually disappears, and the material returns to a transparent state. During the cooling process, the PA recrystallizes to form new scattering centers, and the material reverts to a misted state. Therefore, the material of this invention can achieve reversible cyclic conversion between the transparent and misted states through a phase transition process.

[0042] The aforementioned transparency-fogging conversion does not rely on dye color change, electrochromic or thermochromic mechanisms, but rather originates from the reversible change in the number and spatial distribution of scattering centers during the crystallization and melting of phase change components, thus realizing the synergistic coupling of phase change heat storage function and optical control function.

[0043] (6) Analysis of microstructure and confined crystal structure To verify the regulatory effect of the gradient annealing-induced restricted crystallization strategy of this invention on the crystallization behavior of phase change components, the obtained samples were observed by scanning electron microscopy (SEM), and the results are as follows. Figures 4-6 As shown.

[0044] Figure 4 This is a SEM image of the microcrystalline structure of the thin film in the atomized state of this invention. After gradient annealing, PA forms a confined microcrystalline structure in the OBC / PVB dual-network system with a size significantly smaller than that of conventional melt-cooled samples. The sample of this invention forms a large number of uniformly distributed submicron-sized crystals, with their size mainly distributed in the range of 100–500 nm, averaging approximately 280 nm.

[0045] Figure 5 This is a SEM image of the transparent microcrystalline structure of the thin film of this invention. Because the crystallite size is lower than or close to the visible light wavelength scale (380-780 nm), the internal light scattering of the material is significantly reduced, thereby achieving high light transmittance.

[0046] Figure 6 This is a SEM image of the microcrystalline structure of a conventional non-transparent phase change material without gradient annealing. In contrast, the control sample without gradient annealing exhibits a continuous crystal structure ranging from several micrometers to tens of micrometers in size. These crystals, with sizes on the same order of magnitude as visible light wavelengths, produce a significant Mie scattering effect, giving the material a milky white or translucent appearance.

[0047] SEM results show that the gradient annealing-induced restricted crystallization strategy proposed in this invention can effectively suppress grain growth and construct a uniformly dispersed submicron-scale microcrystalline structure, providing a structural basis for the material to obtain the ability to switch between transparency and fogging.

[0048] (7) Optical and phase transition performance analysis To verify the transparency and temperature response characteristics of the material of this invention, the sample was visually observed and its thermal properties were tested. The results are as follows: Figures 7-10 As shown.

[0049] Figure 7 and Figure 8 The images show the appearance of the thin film material in its atomized and transparent states, respectively. When the ambient temperature is below 25°C, PA is in a crystalline state, and a large number of crystal scattering centers are formed inside the material, such as... Figure 7 As shown, it appears as a semi-transparent or atomized state; when the ambient temperature is higher than the phase transition temperature, PA gradually melts, the crystal structure disappears, the refractive index difference within the system decreases, and the material transforms into a transparent state, as shown. Figure 8 As shown.

[0050] Meanwhile, when the sample was observed against different colored backgrounds, the background color was clearly transmitted, demonstrating good light transmittance. After 720 hours of sun exposure, the material still maintained high transparency and flexibility, without obvious yellowing, cracking, or optical performance degradation, indicating its good weather resistance and stability.

[0051] Figure 9 The XRD diffraction pattern of the transparent-to-fog reversible phase change film is shown. The results indicate that the characteristic diffraction peaks of the phase change component and the polymer component are retained in the composite film, and no new crystal phase formation is detected, suggesting that the components mainly form a stable composite system through physical interactions.

[0052] Figure 10 The image shows the DSC test data for the transparent-to-fog reversible phase change film. The results indicate that the phase change temperature is 28.6 ℃, the latent heat of phase change is 115.83 kJ / kg, the specific heat capacity is 3.24 kJ / (kg·K), and the thermal conductivity is 0.33 W / (m·K).

[0053] The results show that the material of the present invention maintains high transparency and good structural stability while still having good heat storage capacity and thermal response performance.

[0054] (8) Verification of glass photothermal regulation performance To verify the thermal regulation capability of the transparent-fog reversible phase change photothermal control film of this invention in transparent enclosure structures, a simulated solar irradiation experimental system was built, and the results are as follows: Figure 11 and Figure 12 As shown.

[0055] Figure 11 This is a schematic diagram of an experimental system for testing the photothermal performance of a transparent-to-fog reversible phase change thin film-glass module. The experimental setup includes a xenon lamp simulating a solar light source, a common transparent glass sheet, the transparent phase change photothermal control thin film of this invention, an ambient temperature chamber, and a multi-channel temperature acquisition system.

[0056] A 2 mm thick transparent phase change photothermal control film was attached to the surface of ordinary glass to form a glass-PCM composite module. A bare glass without PCM coverage was used as a control group. During the experiment, the same irradiation conditions were maintained, and the temperatures of the upper and lower surfaces of the glass, the PCM layer interface, and the ambient temperature were measured.

[0057] Figure 12 The figure shows the experimental results of the photothermal performance test of the transparent-to-fog reversible phase change thin film-glass module. The experimental results show that: 1. The temperature of the upper surface of the bare glass rises to approximately 29°C within 500 seconds; the temperature of the lower surface rises to approximately 27°C within 700 seconds, exhibiting a rapid temperature rise characteristic. In contrast, the glass module covered with the transparent phase change photothermal control film of this invention shows a significant temperature lag around 28.6°C.

[0058] 2. When the temperature approaches the phase transition temperature, the phase transition component absorbs solar radiation heat and undergoes a solid-liquid phase transition, storing a large amount of heat as latent heat in the PCM layer. Therefore, the rate of temperature increase on the glass surface decreases significantly, and the temperature of the lower surface of the glass remains consistently lower than the corresponding location on the bare glass, effectively suppressing heat input to the indoor side. As the irradiation time further extends, the phase transition component gradually completes melting, and the temperature of the glass-PCM module continues to rise.

[0059] Because the PCM layer continuously absorbs and stores solar radiation heat, the overall temperature of the glass-PCM module is higher than that of the bare glass, but the heat transferred to the inside of the glass is reduced. The results show that the thin film of this invention can increase the heat storage capacity of the building envelope through the synergistic effect of latent heat storage of phase change and high sensible heat capacity, reducing the penetration of solar radiation heat into the internal space, thereby reducing the temperature rise of the internal space.

[0060] The results demonstrate that the transparent phase change photothermal control film of the present invention has good light transmission, heat storage and passive thermal management functions, and is suitable for transparent enclosure systems such as automotive glass, building windows, skylights and greenhouse covering structures.

[0061] Example 2: A method for preparing a transparent-atomized reversible phase change photothermal control film based on restricted crystallization regulation, which differs from Example 1 in that: in step (1), eicosane (C20, melting point about 37°C, latent heat of phase change about 247kJ / kg) is used instead of paraffin as the phase change component, and the ratio of OBC and PVB is adjusted to OBC 15 wt%, PVB 10 wt%, and eicosane 75 wt%; no external nucleating agent is added.

[0062] In step (3), the high-temperature homogenization temperature is adjusted to 90-120°C, the nucleation induction temperature is adjusted to 45-55°C, and the remaining steps and parameters are the same as in Example 1.

[0063] The resulting thin film has a phase transition temperature of 36.1℃ and a latent heat of phase transition of 144.7 kJ / kg; the crystallite size ranges from 200 to 600 nm, with an average particle size of 320 nm; it is completely transparent above 36.1℃ and uniformly atomized below 36.1℃, exhibiting good cycle reversibility.

[0064] This embodiment demonstrates that by replacing paraffin with long-chain alkanes with different melting points and adjusting the gradient annealing temperature range, it is also possible to obtain a restricted crystal structure and a reversible transparent-to-fogging conversion function.

[0065] Example 3: A method for preparing a transparent-fogging reversible phase change photothermal control film based on restricted crystallization control. The difference from Example 1 is that in step (4), a low-frequency periodic vibration field is not applied, and the remaining steps and parameters are the same as in Example 1.

[0066] The resulting film still possesses a confined crystalline structure and reversible transparency-fogging conversion characteristics, but the uniformity of crystallite distribution decreases, local crystallite agglomeration occurs, and the crystallite size distribution range expands to 120–640 nm. The transparency-fogging conversion cycle stability is lower than that of Example 1.

[0067] This embodiment demonstrates that low-frequency periodic vibration fields play an important role in promoting uniform distribution of crystal nuclei and suppressing local grain agglomeration.

[0068] Example 4: A method for preparing a transparent-atomized reversible phase change photothermal control film based on restricted crystallization regulation. The difference from Example 1 is that in step (1), nano-silica (particle size 20-50 nm) is further added as an inducing nucleation component, and the amount added is 0.5 wt% of the mass of the phase change component. The remaining steps and parameters are the same as in Example 1.

[0069] The resulting thin film crystallite size was further refined, with the average size decreasing from about 280 nm in Example 1 to about 200 nm. The distribution was more uniform, the transparency-to-fogging conversion response speed was accelerated, and the cycle stability was improved.

[0070] This embodiment demonstrates that the addition of nucleation-inducing components can further increase the nucleus density and refine the grains.

Claims

1. A method for preparing a transparent-to-fogging reversible phase change photothermal controlled thin film based on restricted crystallization regulation, characterized in that, Includes the following steps: (1) The phase change component and the transparent polymer support component are placed in a reaction vessel, heated to a molten state and mixed evenly to obtain a molten mixture; (2) The molten mixture is taken out from the reactor and pretreated by casting at room temperature to obtain a gel-like precursor of phase change controlled film; (3) The obtained gel-like precursor is subjected to gradient annealing, including: a) High-temperature homogenization stage: The film is heated to 10-60°C above the melting temperature of the phase change component and held for 0.5-24 h to promote interfacial reconstruction, chain rearrangement and uniform dispersion between the phase change component and the polymer support component. b) Nucleation induction stage: Cool down to 0-20°C above the crystallization temperature of the phase change component and maintain for 0.5-12 h to induce uniform nucleation and increase the nucleus density; (4) The phase change components are cooled at a rate of 0.1 to 5 °C / min to complete the crystallization process and obtain a transparent-atomized reversible phase change photothermal control film with a restricted crystal structure.

2. The preparation method according to claim 1, characterized in that: The phase change component is a straight-chain alkane, a branched-chain alkane, paraffin, or a mixture thereof with 16 to 40 carbon atoms; the transparent polymer support component includes one or more of olefin block copolymers (OBC), polyvinyl butyral (PVB), polyurethane, and polymethyl methacrylate.

3. The preparation method according to claim 2, characterized in that: The transparent polymer support component includes olefin block copolymer OBC and polyvinyl butyral PVB, and the mass fraction of each component in the melt mixture is: phase change component 65-80 wt%, OBC 10-25 wt%, PVB 5-15 wt%.

4. The preparation method according to claim 1, characterized in that: In step (4), a low-frequency periodic vibration field with a frequency of 20 to 85 Hz is applied synchronously to promote uniform distribution of crystal nuclei, suppress local grain agglomeration and preferential growth, thereby constructing a confined crystal structure.

5. The preparation method according to claim 1, characterized in that: In step a), the annealing temperature of the high-temperature homogenization stage is 80-120°C; in step b), the nucleation induction stage is located near the crystallization temperature range of the phase transformation component, and the number of crystal nuclei, grain size and spatial distribution are adjusted by controlling the residence time.

6. The preparation method according to claim 1, characterized in that: In step (3), an inducing nucleation component is further added, which includes one or more of nano-silica, nano-alumina, nano-cellulose, and graphene quantum dots.

7. A transparent-fogging reversible phase change photothermal control film, prepared by the method described in any one of claims 1 to 6, characterized in that: The film has a confined crystalline structure, wherein the phase change component is uniformly dispersed in the form of submicron-sized microcrystals in the OBC / PVB dual network system, and the size of the microcrystals is 100-500 nm; the OBC / PVB dual network system is composed of olefin block copolymer OBC and polyvinyl butyral PVB, wherein OBC provides a flexible support framework and PVB provides a transparent auxiliary support.

8. The transparent-fogging reversible phase change photothermal control film according to claim 7, characterized in that: The transparent-to-atomized reversible phase change photothermal control film has phase change heat storage, light transmission control and temperature buffering functions. It is transparent when the temperature is above the phase change temperature and atomized when the temperature is below the phase change temperature. The reversible conversion between the transparent and atomized states is driven by the light scattering changes generated during the melting and crystallization of the phase change components.

9. The application of the transparent-fogging reversible phase change photothermal control film as described in claim 7 or 8 in the thermal management of automotive glass, building windows, sunroof glass, greenhouse covering structures, and transparent enclosure structures.

10. The application according to claim 9, characterized in that: The thin film reduces solar radiation heat input and slows down internal space temperature fluctuations through the synergistic effect of phase change heat storage and light transmission regulation.